Risk and consequences of osteoarthritis after a professional football career: a systematic review of the recent literature - Gouttebarge, V.; Inklaar, H.; Frings-Dresen, M. H. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: The aim of the present study was to assess whether previous injury is a risk determinant for knee and ankle osteoarthritis (OA) in former professional football players and to explore OA-related activity and work limitations.